Alterations of serum levels of plasminogen, TNF-α, and IDO in granulomatosis with polyangiitis patients. (December 2021) - Kyurkchiev, Dobroslav; Yoneva, Tsvetelina; Yordanova, Adelina; Kurteva, Ekaterina; Vasilev, Georgi; Zdravkova, Yana; Sheytanov, Ivan; Rashkov, Rasho; Ivanova-Todorova, Ekaterina
Background: Granulomatosis with polyangiitis (GPA) is a representative of vasculitides associated with anti-neutrophil cytoplasmic autoantibodies. "Classical" antibodies directed against proteinase 3 are involved in the pathogenesis and are part of the GPA diagnosis at the same time. Along with them, however, antibodies against Lysosomal-Associated Membrane Protein-2 (LAMP-2) and antibodies directed against plasminogen have been described in GPA. Objectives and methodology: We performed a cross-sectional study enrolling 34 patients diagnosed with GPA. Our study was aimed at looking for correlations between serum levels of LAMP-2 and plasminogen and the clinical manifestations of the GPA. Furthermore, we examined serum levels of tumor necrosis factor-alpha (TNF-α) and its associated indoleamine-pyrrole 2, 3-dioxygenase (IDO), as well as we looked for a correlation between these cytokines and the clinical manifestations of GPA. Results: The results showed that in GPA, serum plasminogen levels were negatively associated with renal involvement (receiver operating characteristic (ROC) area under the curve (AUC) of 0.78) (95% CI 0.53–0.91), p = 0.035, and the extent of proteinuria, Spearman's Rho = –0.4, p = 0.015. Increased levels of TNF-α and IDO correlated with disease activity, Spearman's Rho =0.62, p = 0.001 and Spearman's Rho = 0.4, p = 0.022, respectively, whereas only TNF-α was increased in severe forms of GPA with lung involvement (ROC AUC of 0.8) (95% CI 0.66–0.94), p = 0.005. Conclusions: In this study, we demonstrate the alteration of soluble factors, which play an important role in the pathogenesis of GPA and their relationship with the clinical manifestations of the disease. Our main results confirm the associations of increased secretory TNF-α and some clinical manifestations, and we describe for the first time decreased serum plasminogen levels and their association with renal involvement.